The natural rate of interest and the financial cycle - Georgi Krustev (European Central Bank (ECB), 2018)
I extend the model of Laubach and Williams (2003) by introducing an explicit role for the financial cycle in the joint estimation of the natural rates of interest, unemployment and output, and the sustainable growth rate of the US economy. By incorporating the financial cycle - arguably an omitted variable from the system - the model is able to deliver more plausible estimates of business cycle dynamics. The sustained decline in the natural rate of interest in recent decades is confirmed, but I estimate that strong and persistent headwinds due to financial deleveraging have lowered temporarily the natural rate on average by around 1 p.p. below its long-run trend over 2008-14. This may have impaired the effectiveness of interest rate cuts to stimulate the economy and lift inflation back to target in the immediate aftermath of the GFC.
Keywords: C32; E43; E44; E52; 330; natural rate of interest; output gap; financial cycle; Kalman filter; monetary policy